Three monoclonal antibodies against measles virus F protein cross-react with cellular stress proteins. - Sheshberadaran, H (1984)
In a group of 11 monoclonal antibodies specifically reacting with the measles virus fusion protein, three antibodies also immunoprecipitated other proteins, in particular a 79,000-molecular-weight protein from virus-infected cells. The cross-reacting 79,000-molecular-weight protein was shown to be a virus-induced host stress protein. This protein could be induced by (i) different paramyxoviruses, (ii) heat shock of uninfected HeLa cells, and (iii) 2-deoxyglucose, tunicamycin, or L-canavanine treatment of different mammalian cell lines. Immunofluorescence of stressed HeLa cells localized the cross-reacting host protein(s) mainly in the cytoplasm. The significance of these results in relation to autoimmunity is discussed.